Lectures on public economics - Atkinson, A. B. (Anthony Barnes) 1944-2017; Stiglitz, Joseph E. (Princeton, New Jersey Princeton University Press, 2015)
"This classic introduction to public finance remains the best advanced-level textbook on the subject ever written. First published in 1980, Lectures on Public Economics still tops reading lists at many leading universities despite the fact that the book has been out of print for years. This new edition makes it readily available again to a new generation of students and practitioners in public economics.The lectures presented here examine the behavioral responses of households and firms to tax changes. Topics include the effects of taxation on labor supply, savings, risk-taking, the firm, debt, and economic growth. The book then delves into normative questions such as the design of tax systems, optimal taxation, public sector pricing, and public goods, including local public goods.Written by two of the world's preeminent economists, this edition of Lectures on Public Economics features a new introduction by Anthony Atkinson and Joseph Stiglitz that discusses the latest developments in the field and areas for future research. The definitive advanced-level textbook on public economics Examines the effects of taxation on households and firms Covers tax system design, optimal taxation, public sector pricing, and more Includes suggestions for further reading Additional resources available online"--Provided by publisher.
Part one : The analysis of policy -- Lecture 1. Introduction : Public economics -- Lecture 2. Household decisions , income taxation, and labour supply -- Lecture 3. Taxation, savings and decisions overtime -- Lecture 4. Taxation and risk taking -- Lecture 5. Taxation and the firm -- Lecture 6. Tax Incidence : simple competitive equilibrium model -- Lecture 7. Tax Incidence : departures from the standard model -- Lecture 8. Taxation and debt in a growing economy -- Lecture 9. Distributional effect of taxation and public expenditure -- Lecture 10. Theories of state and public economics -- Part two : Lecture 11. Introduction to part two : normative analysis -- Lecture 12. The structure of indirect taxation -- Lecture 13. The structure of income taxation -- Lecture 14. A more general treatment of the optimal tax problem -- Lecture 15. Public sector pricing and production -- Lecture 16. Public goods and publicly provided private goods -- Lecture 17. Local public goods -- Lecture 18. Public economics : theory and policy.
"Originally published in 1980 by McGraw-Hill."--Title page verso.
"With a new introduction by the authors"--Cover.
Includes bibliographical references (pages 481-507) and indexes.
Keywords: Finance, Public; Welfare economics